Strategic Importance of Corporate Communication and Leadership Styles in the Performance of Slovakian SMEs - Kuczman, Kornél; Jenei, Szonja; Singh, Dhruv Pratap; Cseri, Petra; Poyda-Nosyk, Nina; Varga, Erika; Dávid, Lóránt Dénes (Journal of Ecohumanism, 2024)
Effective internal communication plays a key role in shaping organisational culture, increasing employee satisfaction and improving performance, especially in small and medium-sized enterprises (SMEs). The purpose of this study is to examine the impact of two-way communication and leadership styles on the employees of Slovakian SMEs, with a particular focus on the challenges posed by the pandemic COVID-19. A mixed methodology was used in the research, which included questionnaire data collection and statistical analysis of the results to explore the frequency and effectiveness of communication and the impact of leadership styles on conflict management. The results highlight that assertive communication and two-way information flow help to increase trust and commitment while having a positive impact on employee motivation and job satisfaction. However, hierarchical communication gaps and inappropriate leadership styles often lead to dissatisfaction and inefficiency. The research has also shown that sustainable development goals, such as incorporating the principles of a circular economy, can contribute to increasing the effectiveness of internal communication and strengthening organisational stability. The new communication challenges brought about by the pandemic, including the consequences of remote working such as feelings of isolation and difficulties in information flow, further reinforce the importance of effective management practices and communication strategies. The paper offers practical suggestions for optimising internal communication systems that can help to increase organisational resilience, improve employee well-being and implement effective leadership practices. The results can contribute to the development of communication strategies and the achievement of organisational success in SMEs.